Relationship between nutritional status and anemia incidence in pregnant women at Kelua Health Center 2024 - Auliva, Mira Nur; Puteri, Mahfuzhah Deswita; Mariati, Nelly (Universitas 'Aisyiyah Yogyakarta, 2024)
A low hemoglobin level, known as anemia, raises the risk of maternal and foetal sickness or death and is among the most prevalent nutritional status concerns. The purpose of this research was to identify the rate of anemia among pregnant women in the Kelua Health Center's service area in Tabalong Regency in 2023 and to draw any conclusions about the association between nutritional status and this condition. The study is cross-sectional in nature and employs quantitative methods. The population and sample used the Total Sampling technique, which consisted of 42 respondents, and observations were made in a record book and data was collected using a Spearman rank test. The study's results found that 25 pregnant women with anemia (59.5%) and pregnant women with abnormal nutritional status amounted to 22 people (52.4%). A positive value of 0.573** and a p-value of 0.000<0.05 were produced by the Spearman rank statistical test's examination of the link between the Bebes variable and the bound variable. There was a strong and unidirectional significant relationship between nutritional status and the incidence of anemia in pregnant women in the Kelua Health Center Working Area, Tabalong Regency. Providing knowledge, education and handling about the importance of consuming nutritious food such as the recommendation of the contents of my plate to increase Hb levels in the blood as a treatment for anemia in pregnant women.